ASCORBIC ACID INDUCED LOSS OF AN ANTIBIOTIC RESISTANCE PLASMID IN Serratia marcescens - Potrus, Wameidh (Iraqi Journal of Science, 2024)
Four bacterial isolates Serratia marcescens (S. m.1, S. m.2, S. m3, S. m.4) were tested for their resistance toward ten Antibiotics which consider the most common usage in the hospitals in the country by antibiotic disc method. The isolate S. m.1 was selected according to the antibiotic resistance results since it was resist for several antibiotics and four of these antibiotics were chosen because of the previous researches referred to that these features are carried by plasmid which is Ampicillin, Streptomycin, Tetracyclin and Chloramphenicol and used as a plasmid markers, the DNA of the isolate S. m.1 was contain a plasmid band , the Ascorbic acid used in different concentrations as a curing agent for the bacteria S. marcescens plasmids, the results of the curing experiment showed that the curing of S. marcescens with ascorbic acid was succeeded in 0.67 %, the cured bacteria isolate have lost its ability to resist the four antibiotics which the mother isolate was resist, and the plasmid DNA extraction for the cured bacteria result showed that the cured bacteria have lost the plasmid band which confirm that this plasmid which coded for Antibiotic resistance feature against the four antibiotics mentioned above.